2013
DOI: 10.1007/s11999-013-3178-1
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphaturic Mesenchymal Tumor: Why is Definitive Diagnosis and Curative Surgery Often Delayed?

Abstract: Background Tumor-induced osteomalacia is a paraneoplastic syndrome resulting in renal phosphate wasting and decreased bone mineralization. Phosphaturic mesenchymal tumors represent a rare etiology of tumor-induced osteomalacia. Nonspecific symptoms of fatigue, bone pain, and musculoskeletal weakness make the diagnosis elusive and lead to a delay in surgical treatment. Questions/purposes In this case series, the following three questions were asked: (1) How do the clinical presentation and features of phosphatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 19 publications
2
57
0
Order By: Relevance
“…Moreover, our data revealed that the definite diagnosis and effective treatment of TIO was significantly delayed for years. Our data are consistent with repeated reports of delays in diagnosis, improper treatment and prolonged morbidity of TIO patients [8][9][10][11][12][13]18]. A typical example is a case report from E. Michael Lewiecki and his colleague, describing an unusual TIO case presented with musculoskeletal symptoms and fragility fractures [13].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, our data revealed that the definite diagnosis and effective treatment of TIO was significantly delayed for years. Our data are consistent with repeated reports of delays in diagnosis, improper treatment and prolonged morbidity of TIO patients [8][9][10][11][12][13]18]. A typical example is a case report from E. Michael Lewiecki and his colleague, describing an unusual TIO case presented with musculoskeletal symptoms and fragility fractures [13].…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, missed diagnoses or even misdiagnoses with subsequently diagnostic and therapeutic delay (ranging from 3-19 years) are commonly seen in reported cases of TIO, accompanied by prolonged morbidity and poor prognosis [8][9][10][11][12][13]. This reflects the relatively poor recognition of the rare disease among physicians.…”
Section: Definition Of Misdiagnosis and Missed Diagnosismentioning
confidence: 99%
“…Phosphaturic mesenchymal tumor (PMT) is a rare mesenchymal neoplasm with unpredictable biological behavior that has been associated with oncogenic osteomalacia (OO) [1][2][3]. It is a paraneoplastic syndrome that is considered to be an acquired type of osteomalacia and is caused by a variety of mesenchymal neoplasms [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…As a result there is usually a delay in diagnosis, as long as 15 years has been reported 8 . Moreover the initial presentation is usually vague and medical presentation instead of anatomical 9 . There are various modalities for tumour localization such as routine radiographs, ultrasonography, CECT, magnetic resonance imaging (MRI), whole body technetium scan and octreotide scintigraphy 10,11 .…”
Section: Discussionmentioning
confidence: 99%